PENINGKATAN KOMPETENSI GURU SMP DI KABUPATEN JAYAPURA MELALUI SUPERVISI AKADEMIK BERBASIS COACHING DAN METODE BERDIFERENSIASI - Farida, Nurul; Dwikurnianingsih, Yari; Sanoto, Herry (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2025)
This research aims to examine the effectiveness of coaching-based academic supervision anddifferentiated methods in improving teacher competency in junior high schools in Jayapuradistrict, Papua. Coaching-based supervision is applied to create collaborative and reflectivecommunication between supervisors and teachers, while a differentiated approach allowssupervision to be tailored to individual teacher needs. This research uses a descriptive qualitativeapproach with data collection techniques in the form of in-depth interviews, participatoryobservation and open questionnaires. The research results show that the coaching approach iseffective in identifying teachers' strengths and challenges and improving their skills in teachingand classroom management. The differentiated method allows for more personalized supervision,increasing teachers' self-confidence and reflective abilities. Overall, this research found that bothapproaches were able to create an inclusive and collaborative supervision environment, increaseteacher professional competence, and form a culture of cooperation in schools. These findingssupport the implementation of more adaptive academic supervision in schools to improve thequality of education.